SISTEM KONTROL DAN MONITORING TANAMAN HIDROPONIK BERBASIS INTERNET OF THINGS (IoT) MENGGUNAKAN NODEMCU ESP32 - Hidayat, Muh Adrian Juniarta; Amrullah, Ahmad Zuli (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2022)
The rapid development of Internet of Things (IoT) technology makes its use even more widespread in various fields. IoT is a series of technologies that are combined to create a device that can be controlled remotely via the internet. In this study, IoT technology is applied to control and monitor hydroponic plants using one of the IoT devices, the NodeMCU ESP32. The purpose of this research is to create an automatic nutrition system for hydroponic plants by utilizing various sensors and monitoring the development of hydroponic plants remotely via the internet to see the performance of IoT technology in controlling and monitoring. The results of this study indicate that the application of IoT technology can precisely provide nutrients to hydroponic plants according to the specified time and can transmit data accurately and in real-time via the internet and displayed on web applications that can be accessed from anywhere.